Penerapan Metode TOPSIS Pemilihan Sosial Media Marketing Untuk Penjualan Aksesoris Pariwisata Lombok - Emi Suryadi; Ahmad Yani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Information technology has a major influence on change, this can be seen from the development of technology in the form of hardware or software. Many people use social media as a means of communication, so that Lombok island tourism accessories entrepreneurs make this a market opportunity to increase turnover (income). Lombok's typical accessories are quite well-known in various communities, many of the people's works are unknown to tourists both from within and from abroad. Social media as an alternative choice as a marketing medium, the number of social media makes business people a dilemma to make decisions. The TOPSIS method as a solution to determine the best alternative can be used as a recommendation. The results of the calculation of this method are obtained from one of the respondents' data on the island of Lombok. In this case the social media that has the highest value based on the results of the data obtained is Facebook with a total score (0.98444271167187). The calculation of this method can change depending on the availability of social media data against existing criteria.